The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1136/archdischild-2015-308673
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a 5-year school-based intervention programme to reduce adiposity and improve fitness and lifestyle in Indian children; the SYM-KEM study

Abstract: Design-Non-randomised non-blinded school-based intervention study.Setting-Two schools in the cities of Pune and Nasik, India. Participants-The intervention group comprised children attending one Pune school from 7-10 years until 12-15 years of age. Two controls groups comprised (1) children of the same age attending a similar school in Nasik, and (2) children in the Pune intervention school but aged 12-15 years at the start of the study. Europe PMC Funders GroupIntervention-A 5-year multi-intervention program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 17 publications
1
55
0
Order By: Relevance
“…The studies revealed the main outcomes, including: BMI (kg/m 2 ), waist circumference, skinfold and body fat percentage related to obesity parameters [40][41][42][43][45][46][47][49][50][51][52][53]56], the level of PA [45,[48][49][50][51][52]54,55,57,58] and various variables related to PF components [42,49,[52][53][54]56] during school years. Measurements of MVPA recommended in these studies were interpreted by measuring with the survey method in some studies [40,50,57] and by way of pedometer or accelerometer in some others [44,45,[47][48][49]51,52,54,55,58].…”
Section: Main Outcomes Regarding Obesity Parameters Physical Activitmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies revealed the main outcomes, including: BMI (kg/m 2 ), waist circumference, skinfold and body fat percentage related to obesity parameters [40][41][42][43][45][46][47][49][50][51][52][53]56], the level of PA [45,[48][49][50][51][52]54,55,57,58] and various variables related to PF components [42,49,[52][53][54]56] during school years. Measurements of MVPA recommended in these studies were interpreted by measuring with the survey method in some studies [40,50,57] and by way of pedometer or accelerometer in some others [44,45,[47][48][49]51,52,54,55,58].…”
Section: Main Outcomes Regarding Obesity Parameters Physical Activitmentioning
confidence: 99%
“…In the studies where BMI (kg/m 2 ) measurements were reported, it was found that body mass index was measured by taking height and weight measurements with standard tools. Three studies were also interpreted by measuring waist circumference [42,46,56]. Skinfold measurements were also performed in three studies [49,50,57].…”
Section: Main Outcomes Regarding Obesity Parameters Physical Activitmentioning
confidence: 99%
See 1 more Smart Citation
“…97 Two studies in which yoga practice was a relatively small component of the intervention were also not included. 98,99 The studies in the analyzed publications were conducted mostly in elementary school settings (n = 18), followed by high school (n = 13), middle school (n = 7), and one preschool within an elementary school (n = 1), with the remaining studies examining a combination of grades, primarily elementary and middle school (n = 6 in both elementary and middle school; n = 2 in both middle and high school). Sample sizes (calculated as the total sample of all subjects in all arms completing the intervention) were often small within individual studies, with a median of 74 and a range of 20-660 in the quantitative studies.…”
Section: Review Of Research On School-based Yoga Interventionsmentioning
confidence: 99%
“…They found improvements related to physical activity—more intervention schools adopted physical activity policies and student participation in physical training classes increased significantly in intervention compared to control schools [33]. Next, two schools in Pune and Nasik implemented a five-year school-based intervention that consisted of daily yoga, breathing exercises, physical activity lessons taught in school, healthier school meals, and health and nutrition education for teachers, students, and their families [34]. Results from the study showed that children in the intervention group were more fit than controls in running, long jump, sit-up, and push-up tests.…”
Section: Introductionmentioning
confidence: 99%